2020
DOI: 10.7759/cureus.10054
|View full text |Cite
|
Sign up to set email alerts
|

Role of Biochemical Markers in Invasive Ventilation of Coronavirus Disease 2019 Patients: Multinomial Regression and Survival Analysis

Abstract: Background and objectives Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the pathogen responsible for the coronavirus disease 2019 (COVID-19) pandemic. The disease mainly affects the respiratory system of the patient, in particular, the lungs, which leads to patients presenting with acute respiratory distress syndrome and acute respiratory failure, with 5-15% of patients requiring observation in the intensive care unit (ICU) with respiratory support in the form of ventilation. This study was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…Another study conducted on hematological parameters of COVID-19 patients showed a mean PLR of 152 in non-severe and 257 in severely affected patients, respectively [24]. Another study conducted previously on a similar population revealed follow-ups of severe laboratory markers in recovered and non-surviving COVID-19 patients, with most of the trends were similar to our study [25]. An analysis conducted on 154 ICU admissions of COVID-19 showed APACHE-II score of 15 and SOFA score of 2.62 with significantly higher scores were predictive of mortality [26].…”
Section: Discussionsupporting
confidence: 90%
“…Another study conducted on hematological parameters of COVID-19 patients showed a mean PLR of 152 in non-severe and 257 in severely affected patients, respectively [24]. Another study conducted previously on a similar population revealed follow-ups of severe laboratory markers in recovered and non-surviving COVID-19 patients, with most of the trends were similar to our study [25]. An analysis conducted on 154 ICU admissions of COVID-19 showed APACHE-II score of 15 and SOFA score of 2.62 with significantly higher scores were predictive of mortality [26].…”
Section: Discussionsupporting
confidence: 90%
“…Although, D-dimer was an effective predictor of mortality in COVID-19 specified by various studies [36,37]. Overall, mortality predictions have been mostly associated in the literature with LDH, followed by CRP, D-dimer, moderately associated with NLR and PCT, and least associated with serum ferritin [38,39]. There were a few limitations of our study, we did not utilize the measurement of oxygen saturation of arterial blood gases as a partial oxygen pressure (arterial PaO2) but instead as pulse oximetry.…”
Section: Discussionmentioning
confidence: 99%
“…Fang, Li [ 17 ] reported that male gender and COPD is associate with increased risk of invasive ventilation, however, this data is not evaluated in terms of mortality. The findings from the study by Asghar, Haider Kazmi [ 18 ] concluded that urea, creatinine, sodium, CRP and lactate dehydrogenase are significant markers of invasive ventilation. Among these markers, D-dimer, hypernatremia, procalcitonin, neutrophilia, leukocytosis, and serum urea can predict mortality in these patients.…”
Section: Discussionmentioning
confidence: 99%